PEMANFAATAN BAHAN DAPUR SEBAGAI PENANGGULANGAN HAMA UNTUK MENGURANGI KETERGANTUNGAN TERHADAP PESTISIDA KIMIA - Nasha Bagas Prakoso; Vita Aprilina; Yuha Nadhirah Qintharah (PENA DIMAS: Jurnal Pengabdian Masyarakat, 2023)
Horticulture functions to meet physical needs as a source of vitamins, minerals and protein, based on observations in Citeureup 1 Village there are people who carry out horticultural activities but the people in the village still do not use natural biopesticides, with the results of observations and interviews, the Utilization of Kitchen Materials program is realized as Pest Control To Reduce Dependence On Chemical Pesticides. Kitchen ingredients can be used as natural pesticides that can eradicate pests. The method of implementing this program is counseling, training and mentoring. The purpose of this program is for people to switch from using chemicals to natural ingredients and minimize expenses. The method of implementing this program is counseling, training and mentoring which will be carried out to the people of Dusun Citeureup 1 RT 01 and 02 will be implemented through housewives who do cultivation horticulture, farmer groups and village communities with a target of 10 participants. Based on the activity "Utilization of Kitchen Materials as Pest Management to Reduce Dependence on Chemical Pesticides" in Citeureup 1 Hamlet, Kutamukti Village, Kutawaluya District,the result it can be concluded that this community service activity has an impact, namely village communities who are present in activities to gain knowledge and information about kitchen ingredients can It is used as a pesticide to prevent pests in plants. Part of the community has also applied Biopesticides to their plants, which means that the purpose of this activity is to divert the use of chemicals that can be said to be successful.